Do firms use the trade credit channel to manage growth? - Annalisa Ferrando; Klaas Mulier (European Central Bank (ECB), 2012)
While many theories of accounts payable and receivable are related to firm performance, there has not been a direct test whether firms actively use them to manage their growth. We argue that it is not just the accounts payable but also the accounts receivable that matter. While the former help to alleviate imperfections in the financial market, the latter do so in the product market. Using over 2.5 million observations for 600.000 firms in 8 euro area countries in the period 1993-2009, we show that firms use the trade credit channel to manage growth. In countries where the trade credit channel is more present, the marginal impact is lower, but the total impact is still bigger. Further, firms that are more vulnerable to financial market imperfections, and therefore more likely to be financially constrained, rely more on the trade credit channel to manage growth. Finally, we show that also the overall conditions of the financial market matter for the importance of the trade credit channel for growth.
Keywords: C23; E44; G32; L25; 330; accounts payable; accounts receivable; Firm performance; trade credit